2021
DOI: 10.3389/fdgth.2021.661708
|View full text |Cite
|
Sign up to set email alerts
|

What Makes for a Successful Digital Health Integrated Program of Work? Lessons Learnt and Recommendations From the Melbourne Children's Campus

Abstract: Embedding digital technologies in healthcare has the potential to streamline and personalize medical care. However, healthcare systems are often fragmented, and therefore achieving a truly integrated digital health program can be challenging. To promote a streamlined, evidence-based approach to implementing digital health solutions in a healthcare system, the Murdoch Children's Research Institute (MCRI) established the Digital Health Translation and Implementation Program (DHTI) bringing together clinicians, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In a study that explores the views of 26 healthcare leaders including managers and quality developers in the county council healthcare organization, the incongruence between the pace of technological development and the implementation of laws and policies is perceived to be a challenge in the implementation of AI in the local healthcare system (Petersson et al, 2021). Additionally, the need to provide students with relevant opportunities in preparation for careers in healthcare digitalization, and the bene ts of a strong and integrated technological infrastructure, have also been recognised in the U.S and Australia (Banerjee et al, 2015;Hourani et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In a study that explores the views of 26 healthcare leaders including managers and quality developers in the county council healthcare organization, the incongruence between the pace of technological development and the implementation of laws and policies is perceived to be a challenge in the implementation of AI in the local healthcare system (Petersson et al, 2021). Additionally, the need to provide students with relevant opportunities in preparation for careers in healthcare digitalization, and the bene ts of a strong and integrated technological infrastructure, have also been recognised in the U.S and Australia (Banerjee et al, 2015;Hourani et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For digital support apps to be implemented, they require integration within current healthcare systems and work ows, which is notoriously challenging. However, studies have suggested that the restructuring of healthcare work ows is even more challenging and that embedding technologies within existing systems is the preference [52,53]. Integration of such tools has the potential to allow for asynchronous communication, remote monitoring, and continuous care.…”
Section: Discussionmentioning
confidence: 99%
“…The healthcare community is repeatedly excited by the hope of providing better care through effective technology adoption [ 7 , 20 , 21 , 22 , 23 , 24 ]. There is no denying that digital health has not been delivered, and digital health has not transformed the health system.…”
Section: Uncertainty In the Healthcare Sector: Digital Health Has Fai...mentioning
confidence: 99%
“…Numerous regulations and standards are relevant to digital health solutions [ 7 , 24 , 196 ]. Regulations must provide life cycle requirements for developing medical software, such as that found within medical devices, and communicating electronic health record (EHR) information [ 197 ].…”
Section: Challenges In Healthcare Systems That Need To Be Accounted F...mentioning
confidence: 99%